Sentidos discursivos das concepções de formação e profissionalização docente: graduandos(as) do curso de Pedagogia da FE/UFG - Jesus, Beatriz Gontijo de (2018)
This dissertation is linked to the research line “Teachers’ Formation, Professionalization, and Educational Work” from PPGE/FE/UFG, and it is also part of Redecentro – Network of Researchers about teachers from the Middle Eastern region of Brazil. Guided by the dialectical historical materialism method, discussing the theme: the discursive meanings formation and professionalization of the beginners and graduating students’ from the undergraduate program Pedagogia, from FE/UFG, year of 2017; the methodology used was a questionnaire, with both open and closed types of questions. In the research, the goal is to answer the following questions - what are the discursive meanings about the conceptions of the formation and professionalization of the beginner and graduating teacher-students from the undergraduate program Pedagogia, from FE/UFG? Which kinds of discursive meanings do the students reveal? The main goal was to identify, to analyze, and to comprehend the discursive meanings about the beginners and graduating teacher-students formation and professionalization among the undergraduate students from the program Pedagogia, from FE/UFG, year 2017; and how the specific goals were to analyze and comprehend the constitution of the public university, the historic process of the teachers’ formation and professionalization, in special the teacher graduated from the program Pedagogia, as well as how to describe, analyze the discursive meanings and to comprehend the socioeconomic profiles of the of the teacher-students surveyed and the other data collected with the answers to the questionnaire questions. It was considered the influence of the educational politics, throughout a bibliographic survey and a documental research. It is discussed, through the chapters, the repercussions of the most recent educational reforms about the public universities and the teachersstudents’ education, formation and professionalization, from undergraduate students from the program Pedagogia, from FE/UFG. The social political historicity from the country is resumed with the intent of highlighting how the changes occurred reshaped the formation of the teachers and, therefore, the Brazilian educational system through its reconceptualization as merchandise, removing, this way, the formation as well as the education of their character of social rights, in which the main requirement would be the performance of conscious and emancipated teachers. Entailing into the achievement of a lightened and hegemonic formation, focused on fulfilling the interests of Multilateral Organisms, overvaluing the practice, efficiency, competency, and efficacy. Stating, like this, the alienation of the individuals in the process that modifies the social functions of the teachers. This reality is also reinforced in the teachers’ professionalization processes, with the finality that they follow the neoliberal ideological discourse that excludes their identity and group conscience. Through the data analysis, it is understood the need of the implementation of discussions, during the undergraduate program Pedagogia from FE/UFG, about the contradictions and ideological disputes found in the public university, also the conception of the formation and, specially, a teachers’ professionalization against hegemonic ideals, which would bring up not alienated, critics, questioners and autonomous individuals. Through this work with subjective meanings it was possible to also identify the existence of gaps in the discourses of the researched students, in terms discussed, such as teaching, social function of the schools, educational work, research and curriculum, therefore it was noticed the need of rethinking about those themes during the undergraduate program.